Prevalence of Hydatid Cysts in Livestock Animals in Xinjiang, China - Qingling, Meng (The Korean Society for Parasitology and Tropical Medicine, 2014)
Hydatid worms, hosted by humans and animals, impose serious human health risk and cause significant livestock production loss. To better understand the disease infection status in Xinjiang, China, we investigated the disease epidemics in 4 livestock animals, i.e., cattle, sheep (both sheep and goat), camels, and horses, slaughtered at the abattoirs in Urumqi, Yining, Tacheng, and Altay areas. The results showed that the animals were infected at different rates, in the order of sheep (9.8%), cattle (8.4%), camels (6.8%), and horses (4.3%). The infection rates were found to be different between the abattoirs in various regions even for the same animals. For sheep, the rates increased significantly as the animals grew older. It was 1.9% before 1 year of age and increased to 8.2% in the age of 1-2 years, and further increased to 12.3% when the animals were 3-4 years old, and reached 17.2% when they were 5-6 year old. Sheep older than 6 years had an infection rate of 19.5%. This study demonstrates that the 4 livestock animals in the pastoral areas in Xinjiang were infected by the parasites to various extend. This study is the first systematic investigation of the hydatid worms in various livestock animals in Xinjiang, China, which provides epidemiological information about the infection of hydatid worms in livestock, and is valuable in developing strategies for prevention and control of the hydatid disease.